Developmental Genomics of Ascidians - Satoh, Noriyuki (Wiley, 2013)
The simplicity and lack of redundancy in their regulatory genes have made ascidians one of the most useful species in studying developmental genomics. In Developmental Genomics of Ascidians, Dr. Noriyuki Satoh explains the developmental genomics of ascidians, stresses the simplicity of Ciona developmental system, and emphasizes single-cell level analyses. This book actively accentuates the advantages of using ascidians as model organisms in an up-and-coming field of developmental genomics.